MEANS OF PHYSICAL THERAPY APPLIED IN RECOVERY AFTER THE SURGERY OF ANTERIOR CROSSING LIGAMENT - BENEDEK FLORIAN (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
What is about to be presented underlines the clarity of the most important issues of physical therapy intervention in sports traumatology and not only, aspects sustained in paper's context. With the help of physiotherapist G.M. and through a unique practical experience, I had the opportunity to collect information and to process them in this context. The paper is based on data obtained during anamnesis, but also from studying the mechanisms production, relevant aspects in a clinical examination functional and complex, and data from specialized books. In this paper I tried to reach both the starting point (choice of treatment) but also the selected means in order to reach a better efficiency of the program of physical therapist treatment.